Institutional distraction and illegal business practices: The role of career concerns and wealth incentives - Neukirchen, Daniel; Köchling, Gerrit; Posch, Peter N. (Journal of Financial Stability, 2025)
We exploit exogenous shocks to institutional investors’ portfolios to show that managers engage in significantly more stakeholder-related misconduct when institutional investors are distracted. Additional cross-sectional tests reveal that managerial career concerns and risk-taking equity incentives strongly moderate this relationship, suggesting that managers weigh the potential benefits and risks before engaging in misconduct during these periods. Finally, we provide evidence that the results are more pronounced when especially those institutional investors who are likely to be motivated monitors of the managers become distracted.